2016
DOI: 10.1002/cmdc.201500550
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Osteogenic Oxysterols as Hedgehog Pathway Activators

Abstract: Oxysterols (OHCs) are metabolic byproducts of cholesterol that are known to function as agonists of the Hedgehog (Hh) signaling pathway. Previously, we reported 23(S)-hydroxycholesterol [23(S)-OHC, 4] as a potent activator of Hh signaling with the ability to functionally differentiate mouse embryonic fibroblasts to an osteogenic fate. To obtain 23(S)-OHC in quantities suitable for in vivo evaluation, we developed a revised synthetic route that decreases the number of steps and chromatographic purifications, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…Oxy234 is a 20(R)secondary alcohol, expectedly displaying an extended side-chain conformation. Accordingly, both Oxy43 and Oxy234 are devoid of significant Hh pathway inhibitory properties and display weak Hh pathway stimulation instead (unpublished observations) [68]. We found that Oxy43 and Oxy234 both possess significant anti-inflammatory properties, with Oxy43′s effects being similar to and Oxy234′s effects slightly weaker compared to Oxy210 (Figure 6).…”
Section: Genementioning
confidence: 62%
“…Oxy234 is a 20(R)secondary alcohol, expectedly displaying an extended side-chain conformation. Accordingly, both Oxy43 and Oxy234 are devoid of significant Hh pathway inhibitory properties and display weak Hh pathway stimulation instead (unpublished observations) [68]. We found that Oxy43 and Oxy234 both possess significant anti-inflammatory properties, with Oxy43′s effects being similar to and Oxy234′s effects slightly weaker compared to Oxy210 (Figure 6).…”
Section: Genementioning
confidence: 62%